The influence of social media on the decision to boycott Israel-affiliated products among the Muslim community in Jabodetabek - Syarif, Muhyiddin; Herman, Sebastian (Journal of Islamic Economics Lariba, 2024)
IntroductionThe recent escalation of the conflict between Israel and Palestine triggered a global solidarity movement, including Boycott campaigns against products affiliated with Israel.ObjectivesThis study aims to analyze the determinants of digitalization's influence on online boycott product buying behavior among Muslim communities in Jabodetabek (Jakarta–Bogor–Depok–Tangerang—Bekasi), the Jakarta Metropolitan Area, or Greater Jakarta. MethodThis study's hypothesis is that social media, religiosity, subjective norms, behavioral control, and attitude have a positive and significant influence on boycotting behavior. It used an online survey with a randomly selected sample of 100 respondents. To test the hypothesis, it used structural equation modeling (SEM) with partial least squares (PLS).ResultsThe results show that social media and religiosity have a positive and significant influence on boycotting attitudes, while subjective norms and behavioral control do not have a significant influence on boycotting attitudes. Boycotting attitude also has a positive and significant influence on buying behavior. The R-square value of the model is 0.763, which means that the independent variables can explain 76.3% of the variability of buying behavior. ImplicationsThis study also provides implications for marketers and policymakers to understand the factors influencing the attitude and behavior of boycotting products affiliated with Israel among Muslim communities in Jabodetabek.Originality/NoveltyThis study contributes to the literature on consumer behavior, especially in the context of boycotting products related to political and religious issues.